An efficient hybrid algorithm for balancing the load of wireless local area network. (November 2016) - Hu, Kai-Cheng; Wang, Shih-Wei; Chiang, Ming-Chao; Tsai, Chun-Wei
Highlights: An efficient and effective genetic algorithm for WLAN load balancing called MMM-GA is proposed. Simulations show that MMM-GA provides a higher bandwidth than GA. Simulations show that MMM-GA takes much less computation time than GA. Graphical abstract: Abstract: Although the IEEE 802.11 wireless local area network (WLAN) provides users of mobile device a convenient method to connect to the Internet, the load of access points (APs) may have a strong impact on the performance of a WLAN, such as the congestion problem. To avoid this issue and to maximize the performance and scalability of a WLAN, an effective method for balancing the load of APs, called a modified multiple-search multi-start framework based micro-genetic algorithm, is presented in this paper. Simulation results show that the proposed algorithm gives a much better solution than the original genetic algorithm does in terms of both the quality and the computation time.